Connections between the mechanical properties of wheat - Szabó Balázs Pál (2012)
The new method was developed, with which we can directly determine the breaking force and the breaking work, needed for snapping a kernel, and a parameter that gives information about the kernel flexibility (deformation modulus). To determine these values, we developed a measuring method, with which a single kernel can be measured. For this task we considered the measuring equipment Lloyd 1000 R to be appropriate, which is a precision stock measurer. We compared the results with outcomes from other kernel hardness measuring techniques (Perten SKCS 4100 machines). The significant level was 95%. The Lloyd instrument measures the pressure power on the kernel, due to the way that the pressure head has taken. The machine records data during the measurement, and draws the load - extension curve (with mm on the X axis and Newton on the Y axis). According to data we can instantly see the measure of power, which the kernel can not withstand and it snaps. Due to the 0 N and max. N values of the diagram and the path related to them, the max. power to snap a kernel can be determined, further called as snapping power and the snapping labour related to it, which is given by the field under the curve. From the power, path curve, the deformation modulus can be determined. The experiment was carried out on horizontally and vertically set crops as well. We tested two different sample sets, adjusted on different levels of moisture. Sample mark "A" was called "air-dry" (10.59% moisture content) and the "B" sample had 13.52 % moisture content. From the Hardness Index and the quasi static procedure we found that, with sample set mark "A",in case of "air-dry" set (moisture content 10,59%), the vertical experiments were more useful, in kernel hardness assortment, than experimenting in a horizontal position. We found that, the hardness index of the kernel with the average moisture of 10.6%, in vertical compression procedure, with the breaking work, has tight, and with the breaking force, has acceptable correlation. In case of sample set "B" (13.52% moisture content) Hardness Index has a close relationship with the deformation modulus of compression procedure in vertical procedure, with breaking force and the breaking work. Flardness Index has a close relationship with deformation modulus measured on horizontal compression procedure, and an acceptable relationship with breaking force. There has been a correlation between the Hardness Index measured by SKCS 4100 equipment and some of the mechanical characteristics of the wheat measured by Lloyd 1000R equipment when investigating a group of soft and hard- wheat varieties. A strong correlation was found between the Harness Index and the deformation modulus (R: = 0.813), between the Hardness Index and breaking force (R: = 0.882), and also a strong correlation between the Hardness Index and the breaking work (R: = 0,881) in the case of samples that have 13 % moisture content in average. A strong correlation was found in the case of samples that had 10.6 % moisture content in average between the Harness Index and the breaking work measured (in the vertical state) by the compression method (R: = 0.791), and a good correlation between the Hardness Index and the breaking force (R: = 0,690).